Demographic variation and socioeconomic inequalities in all forms of malnutrition among children aged 6 months to 9 years: findings from the Vietnamese General Nutrition Survey 2020 - J Bernadette Moore; Xiaodong Lin; Louise Dye; Van Khanh Tran; Yun Yun Gong; Xiaomian Tan; Pui Yee Tan; Somphos Vicheth Som; Son Duy Nguyen; Do Tranh Tran; Nga Thuy Tran; Samantha Caton; et al. (BMJ Public Health)
Introduction The double burden of malnutrition (DBM) is a global public health challenge. This study examined the prevalence of population-level DBM, its demographic and socioeconomic determinants as well as the associations between anthropometric indicators of undernutrition and overnutrition, and micronutrient deficiencies (MNDs), among Vietnamese children, using the data from the nationally representative General Nutrition Survey 2020.Methods Data on anthropometric parameters, micronutrient biomarkers, demographic and socioeconomic indicators for 7289 children aged 6 months to 9 years were analysed. Determinants of malnutrition were assessed using logistic regressions, reported as OR with 95% CIs.Results At national level, 12.7%, 10.5% and 4.7% of children were stunted, underweight and wasted/thin, while 7.3% and 7.1% were overweight and obese, respectively. Low serum zinc, anaemia and iron deficiency were the common MNDs observed, affecting 53.1%, 15.2% and 13.9% of the study participants. Older children aged 2–4 years (OR (95% CI) 1.43 (1.20, 1.72)), ethnic minorities (5.94 (3.78, 9.36)) and those living in mountainous areas (5.06 (1.18, 14.42)) had increased odds of stunting, whereas reduced odds were found in children from the richest quintile (0.13 (0.05, 0.32)). Similar determinants were associated with underweight and MNDs. Males (1.43 (1.16, 1.76)), children aged 5–9 years (10.02 (6.71, 14.97) and children from the richest quintile (2.91 (1.20, 7.05)) had increased odds of overweight. Children with anaemia, low serum retinol and low serum zinc had increased odds of stunting and underweight than non-micronutrient-deficient children (adjusted OR=1.43–1.71). Compared with children without MNDs, those with ≥3 MNDs had almost double the odds of stunting and underweight, whereas those with ≤3 MNDs had reduced odds of overweight (adjusted OR=0.38–0.60).Conclusions Significant demographic variation and socioeconomic inequalities in child malnutrition were identified. National policies and programmes in Vietnam should address age-specific, sex-specific, geographical and socioeconomic disparities to accelerate progress in reducing child malnutrition.